Волшебное слово: рассказы и сказки / В. Осеева - Осеева Валентина Александровна (Школьная библиотека, 2007)
Экземпляры: ф. 4 (20090608) / Инвентарный номер: 93375 / Цена: 73.00 / Авт.знак: О-72 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6